Kritik Teologis dari Perspektif John Calvin terhadap Pemikiran Walter Lippmann tentang Neoliberalisme - Rinto Fransiscus Pangaribuan (Reformed Center for Religion and Society, 2023)
Neoliberalism becomes a problem in the socio-political reality in Indonesia because it changes the role of lawand government as market servants. As a result, government policies often put business interests above public interests. However, the attitude of Christianity towards neoliberalism is still ambiguous because some consider it to be in harmony with Christianity, while the rest argue otherwise. Therefore, this study aims to analyze neoliberalism to resolve this ambiguity. To fulfill the purpose of the study, the authors collected data using the literature study method. Walter Lippmann's work became the focus of investigation because his ideas were pioneers of the development of neoliberalism. Meanwhile, John Calvin's theology is used as a lens to criticize neoliberalism. The results show that neoliberalism aims to organize the orientation of law and government to align themselves withmarket interests. If harmony has been achieved, Lippmann believes individual freedom is automatically realized.After comparing it with Calvin's theology, the author argues that neoliberalism contradicts Christianity becauseit has reduced human nature to a mere economic instrument. Thus, the attitude of Christianity is to monitorneoliberalism with criticism to anticipate its negative impact on society.